Phylogenetic taxon definitions for Fungi, Dikarya, Ascomycota and Basidiomycota - David S. Hibbett; Meredith Blackwell; Timothy Y. James; Joseph W. Spatafora; John W. Taylor; Rytas Vilgalys (IMA Fungus)
Abstract Phylogenetic taxon definitions (PTDs) are explicit, phylogeny-based statements that specify clades. PTDs are central to the system of rank-free classification that is governed by the PhyloCode, but they can also be used to clarify the meanings of ranked names. We present PTDs for four major groups: Fungi, Dikarya, Ascomycota, and Basidiomycota.